The Green Revolution : A Personal View of the United Nations at work - Johnson, Stanley (London: Hamish Hamilton Publishers, 1972)
This book examines Green revolution, Food and Agricultural Organisation's provisional indicative world plan for agricultural development (IWP). It focuses on food, employment, urbanization. The book further identifies challenges like huge social, technical and economic hurdles that need to be overcome before the full potential of the new agricultural technology can be realized.
Includes index
lje 03/07/17
Loans
Keywords: United Nations; Agricultural Development; Green Revolution